INOVASI PELAYANAN ADMINISTRASI MELALUI WHATSAPP (PANDAWA) PADA BPJS KESEHATAN KOTA PALOPO - Kamal, Kasmad; Drajat, Zakiah; Syah, Syahiruddin (PRAJA: Jurnal Ilmiah Pemerintahan, 2025)
This research was carried out at BPJS Health Palopo City, which aims to find out how PANDAWA service innovation is implemented at BPJS Health Palopo City, using the theory of innovation characteristics according to Rogers in Sukarmin (2020), namely (1) Relative adventage or relative advantage, (2) Compatibility or suitability, (3) Complexity or complexity, (4) Trialability or ability to be tried, and (5) Observability or ease of observation. The type of research used is a descriptive method with a qualitative approach. The results of this research show that the PANDAWA service innovation at BPJS Health Palopo City has been successful, which can be seen from the five indicators used in this research, that the PANDAWA service innovation has relative advantages, where people who use this service can do so only via smartphone. without waiting in line at the office, then it is in line with the needs of people who want to provide services quickly, then the complexity only arises from technical problems in using PANDAWA services, namely network problems, then the ability to try has provided benefits for the community in using PANDAWA services, and finally ease of observation where the community is very It's easy to use this PANDAWA service.